2016
DOI: 10.1007/s00167-016-4226-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of non-operative treatment for patients presenting SLAP lesions in diagnostic provocative tests and MR arthrography

Abstract: Conclusions Non-operative treatment with an appropriate regimen provided satisfactory clinical outcomes in middleaged patients with symptomatic SLAP lesions and should be considered before recommending operative treatment. Clinical relevance Non-operative management using combined intra-articular corticosteroid injection with rotator cuff and periscapular strengthening exercises could be applied as primary treatment for patients with symptomatic SLAP lesion who participate in recreational level of sports. Leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“… 10 11 Furthermore, satisfactory clinical outcomes have been reported for non-operative intervention as the primary treatment of SLAP lesions. 23 24 Because biceps tenodesis and non-operative intervention have gained popularity for the management of SLAP lesions, the incidence of SLAP repair in Korea is believed to have decreased since 2012. An increasing frequency of SLAP repairs was also reported in the United States before 2010 6 8 9 ; however, a decreasing trend was noted in more recent studies.…”
Section: Discussionmentioning
confidence: 99%
“… 10 11 Furthermore, satisfactory clinical outcomes have been reported for non-operative intervention as the primary treatment of SLAP lesions. 23 24 Because biceps tenodesis and non-operative intervention have gained popularity for the management of SLAP lesions, the incidence of SLAP repair in Korea is believed to have decreased since 2012. An increasing frequency of SLAP repairs was also reported in the United States before 2010 6 8 9 ; however, a decreasing trend was noted in more recent studies.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 In a prospective case series of 46 patients, Shin et al found that three months of non-operative treatment improved patient's American shoulder and elbow surgeons (ASES) scores and Constant scores from baseline by two years after commencement of non-operative treatment. 7 Similarly, Edwards et al, in a case series of 19 patients, found that 3-6 months of non-operative treatment significantly improved patient ASES scores compared with prior to treatment. 8 However, in both studies, several patients (15% and 51%, respectively) still required surgery after this period of non-operative treatment.…”
Section: Introductionmentioning
confidence: 88%
“…8 However, in both studies, several patients (15% and 51%, respectively) still required surgery after this period of non-operative treatment. 7,8 SLAP repair is a commonly advocated surgical treatment for SLAP tears. It involves the reattachment of the superior labra to the glenoid rim.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While repair of Type 2 SLAP lesions was 9.4% of all applicants’ shoulder procedures performed by ABOS Part 2 candidates from 2003 to 2008 [ 20 ], the rate has been diminishing as results of clinical studies indicate that success rates in overhead athletes and in middle-aged patients are lower than expected [ 19 , 21 , 22 ]. Alternative surgical treatments such as bicep tenodesis or tenotomy for the middle-aged population and those with rotator cuff tears have emerged as options preferred by some authors [ 23 , 24 ] and may be applicable for younger athletes as well [ 25 - 27 ]. Others recommend simple debridement of unstable labral tissue in overhead athletes.…”
Section: Introductionmentioning
confidence: 99%